The effect of training based on offensive transition waves on certain physical variables, especially for handball players. Researchers - Amin, Jawan Salahuddin; Muhammad, Prof. Dr. Awat Ahmed Faqi (Sulaimani Journal for Humanities, 2026)
The researchers are investigating the effect of offensive transition wave training on several physical variables, particularly explosive arm and leg power, speed-strength, and transition speed. Since these variables are influenced by various methods, offensive transition exercises may be an effective training approach for improving them, potentially providing essential benefits for handball players. The research aims to develop a training program based on offensive transition waves for specific physical variables, especially for handball players, and to identify differences between pre-tests and post-tests between the experimental and control groups. The researchers employed a two-group experimental design (experimental and control). The sample was selected purposively from 26 players of the Sulaimaniyah Youth Handball Club (under 18 years old). The sample was divided into two groups: an experimental group of 11 players and a control group of 11 players. The researchers concluded that the proposed training program had positive effects on improving the level of the experimental group sample in physical variables compared to the control group that used the traditional training program. The researchers recommended using the proposed training program in training youth handball teams in Iraq, as well as the need for age group coaches (buds, juniors) to pay attention to it.
Keywords: Training based on offensive transitions; physical abilities in handball